'In war-torn Spain': The politics of Irish press coverage of the Spanish civil war. (December 2017) - O'Brien, Mark
The Spanish civil war was a conflict that acted as a touchstone for the divisions within Irish society. As a newly-independent state that was 93 per cent Catholic, reporting a conflict that involved, on the one hand, an armed rebellion against a democratically elected government, and on the other, the killing of clergy and the burning of churches, proved divisive. The decisions by Ireland's three national newspaper titles to send correspondents to Spain only further polarized opinion as their reportage reinforced divergent opinions on the origins and meaning of the conflict. The examination, through digital archives, of the activities of these correspondents sheds new light on the experiences of war correspondents in this conflict and on the 'newspaper war' that sought to influence public and political opinion on it. Similarly, the reactions to these reports give an insight into how divisive the conflict was within a state seeking to bed down its own democratic institutions.